Analisis Pembiayaan Pemilikan Rumah (PPR) Melalui Akad Akad Pada Bank Syariah Indonesia (BSI) KCP LAMPUNG - Nabilah Syafithri; Muhammad Iqbal Fasa; Is Susanto (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This study aims to identify issues related to housing financing (PPR) through murabahah contracts at Bank Syariah Indonesia (BSI). This consider was outlined employing a subjective strategy. Data collection procedures through the method of documentation. Employing a qualitative approach with a case study methodology, data collection was conducted through documentation methods. The validity of the data was ensured using source triangulation, and data analysis followed three stages: data reduction, data presentation, and drawing conclusions. The results indicate that the implementation of Domestic Ownership Financing (PPR) at BSI primarily uses murabahah contracts, complemented by wakalah contracts to enhance the murabahah process. The application of murabahah contracts at BSI adheres to the DSN-MUI fatwa No. DSN-MUI/IV/2000, whereby the bank initiates a wakalah contract before proceeding with the murabahah contract following negotiations with the developer. Several issues arise within the domestic ownership financing process at BSI. For instance, if a client is late in making payments for an extended period, BSI will undertake restructuring or reconditioning. Additionally, if a client wishes to transfer the financing, this is permitted only if the intent is to repay the financing; other reasons are not allowed. In cases of unforeseen disasters, such as the death of a client or house fire, the bank will utilize client securities to settle outstanding financing obligations. Furthermore, an increase in Non-Performing Financing (NPF). To address the rise in NPF, BSI implements measures to mitigate risks by applying the 5C framework before granting financing, which includes Character, Capacity, Capital, Collateral, and Conditions.